Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fpsyg.2019.00567
|View full text |Cite
|
Sign up to set email alerts
|

Facing Anxiety, Growing Up. Trait Emotional Intelligence as a Mediator of the Relationship Between Self-Esteem and University Anxiety

Abstract: The current study analyzed how trait emotional intelligence (trait EI) mediates the relationship between self-esteem and state anxiety and trait anxiety. The sample was composed of 153 undergraduate students from the University of Cádiz, Spain (71.9% women and 28.1% men). Students completed measures of self-esteem, state anxiety, trait anxiety, and trait EI. Mediation analyses were completed with three trait EI dimensions (EA, emotional attention; EC, emotional clarity; and MR, mood repair) as mediating variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
40
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 62 publications
8
40
1
2
Order By: Relevance
“… Pena and Losada (2017) indicated in their mediation model that, in stressful situations, students with higher levels of emotional attention manage emotions less effectively and tend to perceive higher test anxiety. Another recent study has also shown that TEI mediates the relationship between self-esteem and state anxiety in a sample of university students, also confirming a negative association between self-esteem and emotional attention ( Guil et al, 2019 ). The authors also indicated that the effect of self-esteem on emotional attention and its influence on clarity and emotional repair exerted a mediated influence with the power to reverse the positive link between self-esteem and anxiety ( Guil et al, 2019 ).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“… Pena and Losada (2017) indicated in their mediation model that, in stressful situations, students with higher levels of emotional attention manage emotions less effectively and tend to perceive higher test anxiety. Another recent study has also shown that TEI mediates the relationship between self-esteem and state anxiety in a sample of university students, also confirming a negative association between self-esteem and emotional attention ( Guil et al, 2019 ). The authors also indicated that the effect of self-esteem on emotional attention and its influence on clarity and emotional repair exerted a mediated influence with the power to reverse the positive link between self-esteem and anxiety ( Guil et al, 2019 ).…”
Section: Introductionmentioning
confidence: 61%
“…TEI is composed of three dimensions and can be defined as the ability to attend (emotional attention), understand (emotional clarity), and modify (mood repair) emotional states ( Salovey et al, 1995 ). Many studies have confirmed the role of TEI as a predictor of positive emotional states and personal, social, academic, and work success ( Brackett et al, 2011 ; Caruso et al, 2019 ; Guil et al, 2019 ). Research has also shown how emotions and affective states control our health and well-being ( Vera-Villarroel et al, 2019 ; Sarrionandia and Mikolajczak, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…16,17 It is composed of three dimensions: emotional attention (EA) that refers to the degree that people attend to their emotional experiences, emotional clarity (EC) that relates to self-perceptions concerning how clearly individuals understand own and other's emotional states, and mood repair (MR) that represents the self-perceptions regarding the ability to manage emotions. 17 PEI acts as a personal protective factor in children, young people, and adults. [18][19][20][21] This positive association has been confirmed in mental, psychosomatic, and physical health.…”
mentioning
confidence: 99%
“…While some studies suggested a negative relationship between EA, anxiety, and depression in undergraduate students, 26 other authors have found a positive association between EA and anxiety, suggesting that high EA is not necessarily beneficial. 17,27 Attending to EC and MR, research has highlighted a positive association between these constructs and psychosocial adjustment, 28 positive coping, well-being, and quality of life, and a negative association with anxiety and depression in BC patients and undergraduates. 29,30 Altogether, these results seem to confirm that perceptions of emotional abilities are essential contributors to psychological adjustment and positive health outcomes.…”
mentioning
confidence: 99%